Konsep Garapan Tari Siti Manggopoh - Y, Rahmi Davina (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Siti Manggopoh dance is a work of dance that describes the cultural traditions of the Minangkabau people. The process of working on dance refers to understanding the message to be conveyed or the theme, as well as research and techniques in Siti Manggopoh dance. Dance stylists work together with other dancers to formulate ideas, rhythms and visual elements related to dance narratives. The concept of dance work in the world of performing arts, dance stylists and other dancers can express their creativity and culture. Dance work is a form of communication that connects tradition and innovation. The concept of Siti Manggopoh dance consists of ideas, titles, themes, movements, dancers, floor patterns, makeup, fashion, properties, dance accompaniment music, stage and lighting. In this dance work, the concept of work is described.